NOVEL APPROACHES IN ETHOSOMAL DRUG DELIVERY: APPLICATION IN DERMATOLOGY AND BEYOND - NEGI, SIMRAN; VERMA, SHALU; RAJ, PRAYAG; SINGH, ALKA (International Journal of Applied Pharmaceutics, 2025)
Skin is a complex and dynamic structure with multiple layers, and it is the body's largest organ. It is the protective barrier between the external and internal environment; it comprises three layers (epidermis, dermis, and hypodermis). The skin performs various vital functions in the body. A conventional drug delivery system (CDDS) is the method of administering drugs into the body through oral, parenteral, and topical administration. This delivery system has several drawbacks, including low bioavailability, uncontrolled release, and poor solubility. A novel carrier and TDDS (Transdermal Drug Delivery) systems were introduced to overcome these drawbacks. It is an advanced drug delivery system designed to overcome the drawbacks of conventional methods and improve therapeutic outcomes. Some examples of novel and transdermal carriers are liposomes, niosomes, ethosomes, and microspheres. Ethosomes are preferred over liposomes and niosomes due to their high ethanol content, which enhances skin penetration and allows deeper drug delivery. TDDS delivers drugs into the deeper layer of the skin and provides a therapeutic effect by avoiding first-pass metabolism. They are generally used to treat various diseases. Ethosomes are highly advanced lipid-based nano-carriers designed to improve transdermal and dermal drug delivery systems. The main aim of writing this review paper is to summarize the focus on the key aspects, such as types of ethosomes, the mechanism of action of ethosomes, the method of preparation, composition, application, characterization, the patent, marketed formulation, and factors of ethosomes.